# Solve for u 15=-5/4u 15=-54u
Rewrite the equation as -54u=15.
-54u=15
Multiply both sides of the equation by -45.
-45⋅(-54)⋅u=-45⋅15
Simplify both sides of the equation.
Simplify -45⋅(-54)⋅u.
Cancel the common factor of 4.
Move the leading negative in -45 into the numerator.
-45⋅(-54)⋅u=-45⋅15
Move the leading negative in -54 into the numerator.
-45⋅-54⋅u=-45⋅15
Factor 4 out of -4.
4(-1)5⋅-54⋅u=-45⋅15
Cancel the common factor.
4⋅-15⋅-54⋅u=-45⋅15
Rewrite the expression.
-15⋅-5⋅u=-45⋅15
-15⋅-5⋅u=-45⋅15
Cancel the common factor of 5.
Factor 5 out of -5.
-15⋅(5(-1))⋅u=-45⋅15
Cancel the common factor.
-15⋅(5⋅-1)⋅u=-45⋅15
Rewrite the expression.
-1⋅-1⋅u=-45⋅15
-1⋅-1⋅u=-45⋅15
Multiply.
Multiply -1 by -1.
1⋅u=-45⋅15
Multiply u by 1.
u=-45⋅15
u=-45⋅15
u=-45⋅15
Simplify -45⋅15.
Cancel the common factor of 5.
Move the leading negative in -45 into the numerator.
u=-45⋅15
Factor 5 out of 15.
u=-45⋅(5(3))
Cancel the common factor.
u=-45⋅(5⋅3)
Rewrite the expression.
u=-4⋅3
u=-4⋅3
Multiply -4 by 3.
u=-12
u=-12
u=-12
Solve for u 15=-5/4u

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top